Global fighter jets : Asia, the new centre of gravity? - Bitzinger, Richard A. (2012)
Some of Asia’s aerospace industries are starting work on fifth-generation fighter aircraft. Despite huge technological hurdles, these countries could displace Western Europe as a leading centre of fighter jet development, and possibly one day give the United States some real competition in global markets.